Palliative systemic therapy for recurrent or metastatic nasopharyngeal carcinoma – How far have we achieved?. (June 2017) - Lee, Victor; Kwong, Dora; Leung, To-Wai; Lam, Ka-On; Tong, Chi-Chung; Lee, Anne
Abstract: Nasopharyngeal carcinoma (NPC) is endemic in Southern China, Taiwan, Malaysia, Singapore, North Africa and Alaska. About 30% of NPC patients develop recurrence or metastasis despite initial radical treatment. Palliative chemotherapy is the first-line treatment for inoperable recurrence or distant metastatic disease. However the standard first-line chemotherapeutic regimen is yet to be established until recently gemcitabine and cisplatin has been proven superior to traditional regimen with 5-FU and cisplatin shown in a phase III randomized-controlled trial. Further palliative systemic treatment options including other chemotherapeutic regimens, targeted therapy and more recently immunotherapy have gradually evolved. We provided a comprehensive review on different traditional chemotherapeutic regimens and highlighted the latest chemotherapeutic treatments as well as the latest development of targeted therapies, immune checkpoint inhibitors and other immunotherapeutic options in this setting.